PEMANFAATAN DATA ANALYTICS SOCIAL MEDIA INSTAGRAM DALAM PENINGKATAN EFEKTIVITAS PEMASARAN DI DESA WISATA SAYAN UBUD GIANYAR - Haskara Wijana, Putu; Mega Sari Apri Yani, Ni Wayan; Putu Wahyu Nirmala, Bagus (CV. Lafadz Jaya, 2024)
This study aims to determine the effectiveness of the utilization of social media instagram used as a means of marketing sayan tourist village located in Ubud Gianyar Bali. The method used in this research is a qualitative method that is descriptive in nature and tends to research using data analysis. There are people of Sayan village who are respondents in this study. Based on the research that has been carried out, the use of social media Instagram is very effective as a means of marketing Sayan Tourism Village, this is supported by the respondent's data making social media Instagram as a means of communication and promotion which is very often used to share information about Sayan Tourism Village on social media. The utilization of social media instagram as a promotional media gets a positive response because it attracts a lot of public interest to visit Sayan village. The results showed that the utilization of social media analytics instagram gave a big influence in marketing activities in Sayan tourism village. So it can be concluded that the utilization of data analytic social media instagram as a means of promotion and communication in improving the marketing of Sayan tourism village is very effective.